Internet of Things Smart Gardening in SMK Muhammadiyah 1 Ngoro Jombang - NUR MACHMUDI, MOCHAMAD YUSAK (SAINTEKBU, 2023)
In the increasingly sophisticated and developing technological developments, many people use technology as a tool that can help or facilitate work ranging from studying, completing homework, to gardening by utilizing technology. In the plantation sector, currently most people still use manual methods, one of which is in the process of watering plants. IoT Smart Gardening is one of the applications of Internet of Things (IoT) technology in agriculture. Research methodology is a collection of work steps to facilitate research. Several methodologies are used in compiling this research. Observations are made to check each observation by monitoring the use of the IoT Smart Gardening system and observing the interaction of farmers with the system. The prototype of the automatic plant watering tool or smart gardening that has been designed will be placed near the plants with a maximum distance of 1 meter. To facilitate the work of the sensor, the prototype of the automatic plant watering tool will be placed near the plants or garden so that the sensor works optimally. The results of the research activities that have been carried out by the author on the smart gardening system based on the Internet of Things (IOT) at SMK Muhammadiyah 1 Ngoro can run well in terms of functionality.